2013
DOI: 10.3748/wjg.v19.i28.4552
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of capecitabine and oxaliplatin regimen for extrahepatic metastasis of hepatocellular carcinoma following local treatments

Abstract: CapeOx showed modest anti-tumor activity in metastatic HCC. However, the manageable toxicity profile and the encouraging disease control rate deserve further study for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Previous cohort studies, addressing the role of conventional therapy with capecitabine (alone or in combination regimens), as first-or second-line systemic therapy for advanced HCC, have demonstrated a certain anti-tumor efficacy and low toxicity (Patt et al 2004;Lee et al 2009;He et al 2013). A phase 2 trial, randomly assigning patients to sorafenib or capecitabine, showed a longer overall and progression-free survival of sorafenib patients but an imbalance of C-P class distribution and extrahepatic tumor spread between groups affect the reliability of results (Abdel-Rahman et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous cohort studies, addressing the role of conventional therapy with capecitabine (alone or in combination regimens), as first-or second-line systemic therapy for advanced HCC, have demonstrated a certain anti-tumor efficacy and low toxicity (Patt et al 2004;Lee et al 2009;He et al 2013). A phase 2 trial, randomly assigning patients to sorafenib or capecitabine, showed a longer overall and progression-free survival of sorafenib patients but an imbalance of C-P class distribution and extrahepatic tumor spread between groups affect the reliability of results (Abdel-Rahman et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Capecitabine, a prodrug of 5-fluorouracil (5-FU) metabolized to the active drug preferentially in liver and tumor tissue by thymidine phosphorylase (Walko and Lindley 2005), has been tested as first-and second-line treatment for HCC by some studies, using either the conventional or metronomic approach (Patt et al 2004;Lee et al 2009;Farrag 2012;He et al 2013;Abdel-Rahman et al 2013;Brandi et al 2013;Granito et al 2015;Murer et al 2016;Casadei Gardini et al 2017). The obtained results are sparse and rather conflicting, and only one of these studies compared capecitabine with best supportive care (BSC) in the setting of second-line therapy (Casadei Gardini et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Patients in 9 studies did not receive any systemic chemotherapy, [ 12 20 ] whereas 20.65% patients had completed systemic chemotherapy before 4 weeks in 1 study. [ 6 ] The chemotherapy regimens included FOLFOX4, [ 6 ] GEMOX alone, [ 15 , 19 ] or in combination with cetuximab, [ 12 ] bevacizumab, [ 18 ] sorafenib, [ 20 ] XELOX, [ 13 , 14 ] or in combination with bevacizumab, [ 16 ] or oxaliplatin plus doxorubicin. [ 17 ] The patients continued sorafenib as maintenance therapy after receiving treatment with GEMOX plus sorafenib in 1 study.…”
Section: Resultsmentioning
confidence: 99%
“…However, these findings should be taken cautiously because of the heterogeneity and low quality of the evaluated studies 15 . Other chemotherapy protocols have been employed with some success in term of prolonged survival and in particular of different profile of toxicity 25 , 26 .…”
Section: Discussionmentioning
confidence: 99%